Futures Tools for Intergenerational Equity - Balcom Raleigh Nicolas; Lianaki Dedouli Irianna (UNESCO, 2025)
The tools in this collection are adaptations of well-established and recently invented futures tools. All of them can help you develop capabilities which can help advance equitable, just and fair generational relations: both for currently living generations and for people yet to exist.